A Novel Treatment of Hidradenitis Suppurativa With Radical Unroofing and Deepithelialization - Dylan G. Choi, BS; Christopher D. Liao, MD; Aleksandra Krajewski, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Hidradenitis suppurativa (HS) is a chronic inflammatory disease beginning with hyperkeratosis of the hair follicles in the dermis and leading to inflammation involving adjacent apocrine glands. HS has significant functional and psychological sequelae, but there is currently no standardized algorithm for treatment. For more severe cases of HS, wide surgical excision remains a standard method of treatment to address the underlying fibrosis and sinus tract formation. However, wide local excision to the subcutaneous fat often entails a multistage recovery and is associated with prolonged wound healing and hospitalization. In hopes of decreasing this burden of care and providing a less invasive method of surgical treatment, the authors propose a single-stage operation involving radical unroofing and deepithelialization with simultaneous split-thickness skin grafting.